Sedimentary provenance of the Marília Formation (Bauru Basin), Southeast Brazil - Marques dos Santos, Caio Augusto; Batezelli, Alessandro; Nakasuga, Wagner Massayuki; Resende, Rosana Silveira [UNESP]; Tello Saenz, Carlos Alberto [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP] (Wiley, 2019)
The Marília Formation is a lithostratigraphic unit positioned at the top of the Bauru Group of Maastrichtian age. The present work presents a provenance study of the Marília Formation sandstones through the combined dating of the fission-track method (FTM) and U–Pb, in which individual zircon grains are simultaneously dated by these two methods. Thirty-one zircons were dated in the C5 sample and 26 in the C7 sample for a total of 57 grains. The data demonstrated a wide range of U–Pb ages, presenting maximum and minimum ages, respectively: 2,905 ± 11 and 128 ± 1 Ma for the C7 sample and 2,676 ± 10 and 455 ± 5 Ma for the C5 sample. Regarding the fission-track (FT) ages, they have been grouped into three time intervals, which are associated to geological events relatively well recognized in the published literature: ages younger than 250 Ma (Wealdenian Reactivation); between 250 and 470 Ma (Palaeozoic orogenesis—Ocloyic, Precordilleran, Chanic, and Sanrafaelic); and older than 470 (Precambrian collisions—Brasiliano I, II, and III). There is a predominance of results of Precambrian age using the U–Pb dating, mainly in the Neopalaeoproterozoic, and with FT dating corresponding to the Ocloyic, Precordilleran, Chanic, and Sanrafaelic orogeneses. From the comparison of the results between the two dating methods, the age variations suggest that the zircons originated during the main south-western orogenesis of Gondwana and were reworked during the Palaeozoic and Mesozoic geological episodes. The ages associated to the Upper Cretaceous are related to the tectonic and magmatic activity of the Alto Paranaiba Uplift.
Keywords: Bauru Basin; fission track; Marília Formation; provenance; U–Pb dating